Analisis Penerimaan Persembahan Jemaat Di Gereja Toraja Wala Klasis Sangalla Selatan Sebelum dan Setelah Adanya Pandemi Covid 19 - Putra, Geraldy Pean; Tapparan, Samuel Randy (UKI Toraja Press, 2021)
This study was to determine the acceptance of the congregation's offerings at the Toraja Church of the Wala Klasis Sangalla' Selatan Congregation before and after the Covid-19 Pandemic. The unit of analysis in this study is the Toraja Church of the Wala Klasis South Sangalla Congregation. The data analysis technique used in this study is that in this study the researchers used comparative research to compare the acceptance of congregational offerings at the Toraja Church of the Wala Klasis Sangalla' Selatan congregation before and after the Covid-19 pandemic. The results of the study said that prior to the pandemic, the Toraja Church of the Wala Klasis Sangalla' Selatan Congregation was able to collect offerings that exceeded the operational funding needs of the church itself and experienced a decrease in the acceptance of offerings after the Covid-19 pandemic. Keywords: Acceptance of Offerings, Covid-19 Pandemic, Comparative. Abstrak Penelitian ini adalah untuk mengetahui penerimaan persembahan Jemaat di Gereja Toraja Jemaat Wala Klasis Sangalla’ Selatan sebelum dan setelah adanya Pandemi Covid-19. Satuan analisis dalam penelitian ini adalah Gereja Toraja Jemaat Wala Klasis Sangalla Selatan. Teknik analisis data yang digunakan dalam penelitian ini adalah dalam penelitian ini peneliti menggunakan penelitian komparatif untuk membandingkan penerimaan persembahan Jemaat di Gereja Toraja Jemaat Wala Klasis Sangalla’ Selatan sebelum dan setelah adanya Pandemi Covid-19. Hasil penelitian mengatakan bahwa sebelum pandemi, Gereja Toraja Jemaat Wala Klasis Sangalla’ Selatan dapat mengumpulkan persembahan yang jumlahnya melebihi kebutuhan dana operasional gereja itu sendiri dan mengalami penururnan penerimaan persembahan setelah adanya pandemi Covid-19. Kata kunci : Penerimaan Persembahan, Pandemi Covid-19, Komparatif.